Penerapan media kartu kata bergambar untuk perbaikan keterampilan membaca permulaan siswa sekolah dasar - Anissa Sekar Rahmawati; D Wahyudin; Acep Ruswan (IKIP Siliwangi, 2024)
Reading instruction plays a crucial role, as it can encourage Indonesian children to develop a sense of nationalism. Each student faces their own reading difficulties, such as not recognizing or reading letters, inability to spell syllables, getting stuck on certain words, and struggling with reading simple sentences. Teachers encounter challenges in conveying the material effectively. In this context, instructional media serves as a companion to teachers’ explanations, enabling students to better understand the content provided by the teacher. Instructional media serves as a tool to support learning objectives. One potential solution is implementing reading instruction using picture word cards. The research conducted at SDN 4 Nagri Kaler found that 79.30% of students were categorized as “>70,” indicating they have achieved learning proficiency with a score of 70 or above. Meanwhile, 20.70% of students fell under the “<70” category, indicating they have not achieved learning proficiency as their scores were below 70. Thus, it can be concluded that the picture word card method is effective in enhancing students’ comprehension, speaking skills, engagement, motivation, creative thinking abilities, as well as cooperation and communication skills. This media significantly contributes to improving students’ learning outcomes and creates a more interactive and effective learning environment.